(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
AMAC experienced growth in built-up areas during the past 30 years. The influx of people brought modification in Land Use Land Cover leading to expansion in urban area and conversion from one LULC to another. This has implications on climate of the area. This study assessed urban growth effects on Land Surface Temperature (LST) of AMAC from 1986 to 2016, using remote sensing and Geographic Information System (GIS).ERDAS Imagine 2014 and ArcGIS 10.4.1 softwares were used for processing and classification of the multi-date (1986, 2001 and 2016) satellite imageries. It also used LST data derived from Landsat imageries as well as rate of change in LULC. Simple linear regression was used to establish relationship between urban growth and LST. Results show that the period between 1986 and 2016 witnessed changes in LULC as bare surface increased by 24.28%, built-up areas by 16.43%. However, vegetation decreased by 40.46%, water body by 0.06 % and rocks by 0.19%. The implication of urban growth on LST is an increase in mean LST of built-up areas to27oC, 33oC and 36oC for 1986, 2001 and 2016 respectively with the highest value at city centre due to sparse vegetal cover. LST also increased across different LULC during the three epoch years. In the relationship between LST and urban growth, LST and NDBI revealed strong relationship with coefficient of determination (R²) of 0.9610 for 1986; 0.9576 for 2001and 0.9732 for 2016. These results call for implementation of policies to control rapid urban growth and preserve vegetal covers